(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The evolution of digital financial infrastructure has transformed the global financial landscape, providing new opportunities for payments, investments, and financial services. National stablecoins, digital assets pegged to a sovereign currency and regulated by monetary authorities, have emerged as critical instruments for integrating blockchain technology into national financial systems. This article examines the role of a national stablecoin within Uzbekistan’s digital finance infrastructure, focusing on its impact on investment activity and financial inclusion. It evaluates the potential benefits, including increased efficiency in transactions, reduced costs, and enhanced access to financial services, as well as the risks related to monetary policy, operational resilience, and cybersecurity. The study draws on international experience and policy frameworks to provide recommendations for successful implementation. Findings indicate that a well-designed and regulated national stablecoin can stimulate investment activity, broaden financial inclusion, and strengthen the overall digital financial ecosystem in Uzbekistan.